Organisational readiness for introducing a performance management system - Michael Ochurub; Mark Bussin; Xenia Goosen (SA Journal of Human Resource Management, 2012)
Orientation: The successful introduction of performance management systems to the public service requires careful measurement of readiness for change. Research purpose: This study investigated the extent to which employees were ready for change as an indication of whether their organisation was ready to introduce a performance management system (PMS).